Quantitative analysis of embryogenesis: a perspective for light sheet microscopy - Höckendorf, Burkhard; Thumberger, Thomas; Wittbrodt, Joachim (Developmental cell, 2012)
It is a challenge in developmental biology to understand how an embryo’s genes, proteins, and cells function and interact to govern morphogenesis, cell fate specification, and patterning. These processes span very different spatial and temporal scales. Despite much progress, simultaneous observation of such vastly differing scales has been beyond the scope of conventional microscopy. Light sheet microscopy fills this gap and is increasingly used for long-term, high-speed recordings of large specimens with high contrast and up to subcellular spatial resolution. We provide an overview of applications of light sheet microscopy in developmental biology and discuss future perspectives in this field.
Gesehen am 10.02.2017